Student-Teacher Trust as Predictor of School Well-Being among Madrasah Student - Nurrohmah; Suryani (International Conference on Sustainable Health Promotion, 2023)
School well-being is a situation where students can meet their basic needs while at school, including having, loving, being and health. The social relationships that students have when they are at school are with teachers. This relationship can be well established if it is based on students’ trust in their teachers. This study aims to determine student-teacher trust as a predictor of school well-being in Madrasah X students in Surabaya. The research method used in this study is a quantitative method. Data collection techniques were carried out by distributing questionnaires to 155 students from grades VII to IX with an age range of 12 to 15 years. This study uses the school well-being scale which has 41 items with a reliability coefficient = 0.957 and the student-teacher trust scale has 14 items with a reliability coefficient = 0.862. The data obtained were then analyzed using the Spearman Rank correlation analysis technique. The results of this study indicate that there is a significant relationship between student-teacher trust and school well-being with a correlation value of 0.810 (p = 0.000) which means that the hypothesis is accepted